Digital Economy and Tax Evasion: Analyzing the Role of Tax Authorities in Regulating E-Commerce Transactions - Abdurokhim Abdurokhim (Sekolah Tinggi Agama Islam Kuningan, 2025)
Tax evasion is a major problem in the e-commerce sector. The digital economy has emerged as a promising alternative to the traditional tax system. This study aims to evaluate the effectiveness of tax authorities in regulating ecommerce transactions within the digital economy. The study employs a mixed-methods approach to provide a comprehensive understanding of tax compliance. The data was gathered from 500 participants, including 300 representatives from businesses of various sizes and 200 tax officials from local and national tax agencies across Southeast Asia. The results from regression analysis demonstrated that the presence of a digital tax compliance system was a significant predictor of reduced tax evadesion, accounting for approximately 40% of the variance in compliance behavior among eecommerce businesses. The research highlights that businesses with a higher awareness of tax obligations tend to exhibit better compliance behavior, while the implementation of digital monitoring tools significantly reduces tax aversion cases. The findings also suggest that tax authorities should prioritize outreach programs and invest in data analytics capabilities to keep up with the evolving digital landscape. Tax authorities in developing countries seeking to improve their monitoring capabilities and adapt to the challenges posed by digital commerce will benefit from the use of advanced digital technologies.